Return On Investment Of An Open Loop Wet Scrubber On A Dry Bulk Carrier - Muzhoffar, Dimas Angga Fakhri; Prasetio, Mathias Bimo; Santoso, Muhammad Agung; Nugraha, Muhammad Irfan Septian; Jamil, Muhamad Sabran (Nama Jurnal Akmi, 2024)
With the increasing global focus on emission reduction in the maritime industry, this study evaluates the decision to implement an Open Loop Wet Scrubber system on a 50,000 DWT Bulk Carrier. The primary objectives of this research are to assess the role of scrubbers in supporting operational efficiency and compliance with MARPOL Annex VI regulations, to determine the optimal timing for scrubber installation to minimize financial risks before ship retirement and to compare the economic efficiency of using scrubbers with high sulfur fuel oil (HSFO) against using low sulfur fuel oil (LSFO) without scrubbers. Through operational simulations on coastal and ocean-going routes, the analysis identifies potential savings, calculates return on investment (ROI), and determines the break-even point (BEP). The results indicate that the installation of an Open Loop Wet Scrubber offers significant long-term savings, with the payback period varying based on route selection and fuel strategy. This research provides critical insights for shipping companies seeking to enhance their competitiveness by balancing compliance with environmental regulations and operational efficiency.